Management Analisis Biaya Produksi Pengolahan Tandan Buah Segar PT. Perkebunan Sumatera Utara (PTPSU) Pabrik Tanjung Kasau - Arjuna Arjuna; Adriansyah Simatupang; Annio Indah Lestari Nasution (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The internship was held at PT. North Sumatra Plantation, District Seisuka, Batu Bara Regency, North Sumatra Province on 01 February – 28 February 2023. Purposeof this internship activity is to find out how to analyze the production costs of processing fresh fruit bunches PT. North Sumatra Plantation is a company that engages in the management, processing and marketing of plantation products. Commodities that are cultivated are oil palm, rubber, sugar cane, sweet potatoes and various other plants. Analysis of the production costs of processing fresh fruit bunches. The results obtained from the activity the internship is in the first week until the end of the research is obtained expenditure of goods and entry of goods and analyze the production costs of fresh fruit bunches at PT. North Sumatra Plantation.